2013
DOI: 10.1016/j.biortech.2013.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Swollenin aids in the amorphogenesis step during the enzymatic hydrolysis of pretreated biomass

Abstract: A key limitation in the overall hydrolysis process is the restricted access that the hydrolytic enzymes have due to the macro-and-micro structure of cellulose and its association with hemicellulose and lignin. Previous work has shown that several non-hydrolytic proteins can disrupt cellulose structure and boost the activity of hydrolytic enzymes when purer forms of cellulose are used. In the work reported here, Swollenin primarily disrupted the hemicellulosic fraction of pretreated corn stover, resulting in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
65
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 33 publications
6
65
3
6
Order By: Relevance
“…As previous work had suggested that Swollenin can weaken hydrogen bonding within amorphous regions of cellulose and hemicellulose (8,9,12), it is possible that Swollenin promotes fiber fragmentation by weakening hydrogen bonds and enhancing slippage between adjacent chains within fiber dislocations. This weakening of hydrogen bonding and chain slippage might be sufficient to cause fragmentation within certain severe dislocations, but not within the less severe dislocations.…”
Section: Volume 290 • Number 5 • January 30 2015mentioning
confidence: 98%
See 4 more Smart Citations
“…As previous work had suggested that Swollenin can weaken hydrogen bonding within amorphous regions of cellulose and hemicellulose (8,9,12), it is possible that Swollenin promotes fiber fragmentation by weakening hydrogen bonds and enhancing slippage between adjacent chains within fiber dislocations. This weakening of hydrogen bonding and chain slippage might be sufficient to cause fragmentation within certain severe dislocations, but not within the less severe dislocations.…”
Section: Volume 290 • Number 5 • January 30 2015mentioning
confidence: 98%
“…Recent work has demonstrated that rapid fiber fragmentation at the very early stages of hydrolysis leads to a dramatic reduction in slurry viscosity, which alleviates some of the issues associated with high solids hydrolysis (2). It has been suggested that fiber fragmentation is primarily induced by the endoglucanase family of enzymes (3,4), although other proteins present in the cellulolytic mixture, such as the more recently characterized oxidative enzymes (5,6) and amorphogenesis-inducing proteins (7)(8)(9), have also been shown to contribute to the overall deconstruction process.…”
mentioning
confidence: 99%
See 3 more Smart Citations